INTEGRATED QUALITY MANAGEMENT - KSZTAŁTOWANIE JAKOŚCI PRODUKTU TURYSTYCZNEGO W REGIONIE - Gołembski, Grzegorz (Wydział Prawa i Administracji UAM, 1999)
The aim o f the article is to get a lecturer acquainted with selected new concepts of developing tourism - the result of which is growing necessity to ameliorate the quality itself of tourist product. In this respect a concept of integrated quality management in tourist regions was discussed in the article. Particular importance of a leadership and of determinating o f tourism development strategy in a given region have been stressed. Further - premises of applying such an integrated quality management under present Polish conditions were discussed and, on this occasion, some defaults of this system have been presented.
INTEGRATED QUALITY MANAGEMENT WITH REFERENCE TO TOURISTIC PRODUCT IN A GIVEN REGION